Self-cleaning photovoltaic cable and method for its production

CN117373756BActive Publication Date: 2026-10-13BAOSHENG SCI & TECH INNOVATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311592909.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2026-10-13
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

[0003]针对目前光伏电缆清洗会对其产生危害、产生运行隐患的问题,本发明提供了一种自清洁光伏电缆及其制备方法,通过在护套层表面经由激光蚀刻出三维结构,从而使线缆表面获得超疏水性能,液滴在线缆表面通过滚动的运动形式,附着并带走有机及无机固体颗粒,以达到自清洁的效果

Benefits of technology

1、本发明通过在交联护套层表面激光蚀刻粗糙程度由内向外逐渐递增的三维结构,从而使线缆表面获得超疏水性能,液滴在线缆表面通过滚动的运动形式,向中心区域聚拢成滴,从而使线缆表面获得超疏水性能,液滴在线缆表面通过滚动的运动形式,附着并带走有机及无机固体颗粒,实现自清洁的效果,且具有优异的防水特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117373756B_ABST
    Figure CN117373756B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a self-cleaning photovoltaic cable, and the cable comprises a conductor, a halogen-free crosslinked insulation layer and a halogen-free crosslinked sheath layer. The preparation method comprises the following steps: S1, sequentially coating the halogen-free crosslinked insulation layer and the halogen-free crosslinked sheath layer on the cable conductor, and performing irradiation; and S2, laser etching a concentric pattern on the surface of the halogen-free crosslinked sheath layer, wherein the concentric pattern comprises a non-etching area and at least two etching areas from the center to the outside, and the pulse energy of the etching areas gradually increases from the center to the outside. The three-dimensional structure with gradually increasing roughness from the inside to the outside is etched on the surface of the crosslinked sheath layer, so that the cable surface has super-hydrophobic performance. The liquid drops on the cable surface gather into drops in the form of rolling movement to the central area, so that the cable surface has super-hydrophobic performance. The liquid drops on the cable surface adhere to and carry away organic and inorganic solid particles in the form of rolling movement, and the self-cleaning effect is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to cables, and more specifically, to a self-cleaning photovoltaic cable and its preparation method. Background Technology

[0002] With the continuous development of new energy technologies, the installed capacity of photovoltaic power generation is also increasing. However, after long-term operation, photovoltaic power plants accumulate dust and impurities on the surfaces of various components, which significantly affects power generation efficiency. To ensure the basic power generation level and efficiency of photovoltaic power plants and increase the total power generation, a scientific and reasonable component cleaning plan needs to be developed based on the external environment of the power plant during safe operation and maintenance. The component cleaning process of photovoltaic power plants is usually divided into three operation procedures: sweeping, soil scraping, and washing. As an important component of photovoltaic modules, photovoltaic solar cables inevitably have inorganic and organic matter such as sand and mud adhering to their surfaces. However, since solar photovoltaic cables are laid on the back of photovoltaic panels, they cannot be cleaned. In fact, cleaning photovoltaic modules can damage existing photovoltaic solar cables, shorten their lifespan, and create operational hazards. Summary of the Invention

[0003] To address the problem that cleaning photovoltaic cables can cause damage and operational hazards, this invention provides a self-cleaning photovoltaic cable and its preparation method. By laser etching a three-dimensional structure on the surface of the sheath layer, the cable surface acquires superhydrophobic properties. Droplets on the cable surface adhere to and carry away organic and inorganic solid particles through rolling motion, thereby achieving a self-cleaning effect.

[0004] To achieve the above objectives, the present invention provides a method for preparing a self-cleaning photovoltaic cable, the cable comprising a conductor, a halogen-free cross-linked insulation layer, and a halogen-free cross-linked sheath layer, the preparation method comprising the following steps: S1. A halogen-free cross-linked insulation layer and a halogen-free cross-linked sheath layer are sequentially coated on the outside of the cable conductor, and then irradiated. S2 laser-etches a concentric pattern on the surface of the halogen-free cross-linked sheath layer. The concentric pattern includes a non-etched area and at least two etched areas from the center outwards. The pulse energy of the etched area gradually increases from the center outwards.

[0005] The advantage of the above pattern is that the roughness of different areas gradually increases from the inside to the outside, which is more conducive to water gathering in the central area more quickly and forming water droplets, thus achieving a better self-cleaning effect.

[0006] This invention achieves superhydrophobic properties on the cable surface by laser etching a three-dimensional structure on the sheath layer surface. Droplets adhere to and carry away organic and inorganic solid particles on the cable surface through rolling motion, thus achieving a self-cleaning effect without causing over-crosslinking adverse effects on the irradiated crosslinked halogen crosslinked insulation layer and the halogen-free crosslinked sheath layer.

[0007] Specifically, in step S2, the concentric patterns are concentric circles or concentric regular polygons, with equal spacing between each pattern. Concentric patterns facilitate water gathering into droplets.

[0008] Preferably, the concentric pattern is square. A square pattern helps to further reduce the contact area between the liquid and the surface, making it easier to form an air film and enhancing the overall hydrophobicity.

[0009] Preferably, in step S2, the concentric pattern includes a non-etched area, a first etched area, and a second etched area from the center outwards. The focal length of the laser etching is 100~300mm, the scanning speed is 0.6~0.8mm / s, the etching pulse energy of the first etched area is 120~125µJ, and the etching pulse energy of the second etched area is 160~165µJ.

[0010] Specifically, in step S1, the halogen-free cross-linked insulation layer is extruded onto the conductor by a single-screw extruder. The screw temperature is set to 125±10℃, 130±10℃, 135±10℃, 140±10℃, and 145±10℃, and its thinnest point thickness is guaranteed to be ≥0.5mm.

[0011] Specifically, in step S1, the halogen-free cross-linked sheath layer is extruded over the halogen-free cross-linked insulation layer by a single-screw extruder, and the screw temperature is set to 135±10℃, 140±10℃, 140±10℃, 150±10℃, 150±10℃, 150±10℃, 150±10℃.

[0012] Specifically, in step S2, the irradiation is: irradiation energy of 1.2~2.4MeV, number of operation channels of 24~48, and irradiation dose of 14~15Mrad.

[0013] A second aspect of the present invention provides a self-cleaning photovoltaic cable prepared by the above-described preparation method.

[0014] Through the above technical solution, the present invention achieves the following beneficial effects: 1. This invention achieves superhydrophobic properties on the cable surface by laser etching a three-dimensional structure with gradually increasing roughness from the inside to the outside on the surface of the cross-linked sheath layer. Droplets on the cable surface gather into a droplet in the central area through rolling motion, thus achieving superhydrophobic properties on the cable surface. Droplets on the cable surface adhere to and carry away organic and inorganic solid particles through rolling motion, achieving a self-cleaning effect and having excellent waterproof properties.

[0015] 2. This photovoltaic cable utilizes physical irradiation crosslinking. The crosslinked molecular chains form crosslinked chains, restricting the slippage of macromolecular chains and improving resistance to deformation caused by the external environment. Furthermore, the irradiation crosslinking process maintains high crystallinity, resulting in mechanical properties far superior to those achieved through chemical crosslinking. With appropriate dosage, irradiation crosslinking improves the cable's tensile strength, creep resistance, and modulus to varying degrees, while significantly enhancing heat resistance and stress cracking resistance. Under the influence of radiation, irradiation crosslinking initiates the connection of linear polymer bonds through free radicals or ionic bonds, forming a three-dimensional network structure and increasing the molecular weight. As the number of crosslinked bonds increases, regional network structures gradually form, eventually resulting in a unified network structure. This crosslinked network structure of polymer exhibits properties such as insolubility in solvents and resistance to melting. It alters the intermolecular gaps, making them smaller than the size of water molecules. Ultimately, it achieves resistance to chemical solvents, a certain degree of waterproofing and hydrophobicity, and enables photovoltaic cables to exhibit more complete low-temperature resistance, dynamic penetration resistance to ozone, UV resistance, acid and alkali resistance, and damp heat resistance in special outdoor environments, thereby improving the service life of the cables.

[0016] 3. In a preferred embodiment of the present invention, the concentric pattern is a square. The square pattern is beneficial to further reduce the contact area between the liquid and the surface, making it easier to form an air film and enhance the overall hydrophobicity. Attached Figure Description

[0017] Figure 1 This is a preferred embodiment of the laser etching pattern in the present invention.

[0018] Explanation of reference numerals in the attached figures 1. Non-etched area, 2. First etched area, 3. Second etched area. Detailed Implementation

[0019] The specific embodiments of the present invention will be described in detail below with reference to examples. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0020] In the following embodiments, the conductor is a TJRX type tin-plated Class 5 conductor, the halogen-free cross-linked insulation material includes XLPO irradiated cross-linked polyolefin insulation material, and the halogen-free cross-linked sheath is XLPO irradiated cross-linked polyolefin sheath material.

[0021] Example 1 The specific manufacturing process of self-cleaning photovoltaic cables is as follows: S1. Prepare stranded conductors; S2. Use a Φ45+35 single screw extruder to extrude halogen-free cross-linked insulation. Set the screw temperature to 125℃, 130℃, 135℃, 140℃, and 145℃, and ensure that the thinnest point thickness is ≥0.5mm. S3. Use an 80 single-screw extruder to extrude halogen-free crosslinked sheaths, with screw temperatures set to 135℃, 140℃, 140℃, 150℃, 150℃, 150℃, 150℃. S4. The cable with the extruded sheath is irradiated through a particle accelerator with an irradiation energy of 1.8 MeV, a running frequency of 40, and an irradiation dose of 15 Mrad. S5. The surface of the irradiated cable sheath is laser-etched to create patterns such as... Figure 1 The pattern shown has a focal length of 100mm and a scanning speed of 0.6mm / s. The center of the pattern is the non-etched area 1, the pulse energy of the first etched area 2 is 125µJ, and the pulse energy of the second etched area 3 is 165µJ.

[0022] Example 2 The specific manufacturing process of self-cleaning photovoltaic cables is as follows: S1. Prepare stranded conductors; S2. Use a Φ45+35 single screw extruder to extrude halogen-free cross-linked insulation. Set the screw temperature to 115℃, 120℃, 125℃, 130℃, and 135℃, and ensure that the thinnest point thickness is ≥0.5mm. S3 uses a Φ80 single-screw extruder to extrude halogen-free crosslinked sheaths, with screw temperatures set to 125℃, 130℃, 130℃, 140℃, 140℃, 140℃, and 140℃. S4. The cable with the extruded sheath is irradiated through a particle accelerator with an irradiation energy of 2.4 MeV, a running frequency of 24, and an irradiation dose of 14 Mrad. S5. The surface of the irradiated cable sheath is laser-etched to create patterns such as... Figure 1 The pattern shown has a focal length of 300mm and a scanning speed of 0.8mm / s. The center of the pattern is the non-etched area 1, the pulse energy of the first etched area 2 is 120µJ, and the pulse energy of the second etched area 3 is 160µJ.

[0023] Example 3 The specific manufacturing process of self-cleaning photovoltaic cables is as follows: S1. Prepare stranded conductors; S2. Use a Φ45+35 single screw extruder to extrude halogen-free cross-linked insulation. Set the screw temperature to 135℃, 140℃, 145℃, 150℃, and 155℃, and ensure that the thinnest point thickness is ≥0.5mm. S3. Use an 80 single-screw extruder to extrude a halogen-free crosslinked sheath, with the screw temperature set to 145℃, 150℃, 150℃, 160℃, 160℃, 160℃, 160℃. S4. The cable with the extruded sheath is irradiated through a particle accelerator with an irradiation energy of 1.2 MeV, a running frequency of 48, and an irradiation dose of 15 Mrad. S5. The surface of the irradiated cable sheath is laser-etched to create patterns such as... Figure 1 The pattern shown has a focal length of 200mm and a scanning speed of 0.7mm / s. The center of the pattern is the non-etched area 1, the pulse energy of the first etched area 2 is 125µJ, and the pulse energy of the second etched area 3 is 165µJ.

[0024] Comparative Example 1 The specific manufacturing process of self-cleaning photovoltaic cables is as follows: S1. Prepare stranded conductors; S2. Mix the XLPE cross-linked polyethylene material with the catalyst evenly, and use a Φ45+35 single screw extruder to extrude the cross-linked insulation layer. Set the screw temperature to 125℃, 130℃, 135℃, 140℃, and 145℃, and ensure that the thinnest point thickness is ≥0.5mm. S3. Mix the XLPE cross-linked polyethylene material with the catalyst evenly, and use a Φ80 single screw extruder to extrude the cross-linked sheath layer. Set the screw temperature to 135℃, 140℃, 140℃, 150℃, 150℃, 150℃, 150℃. S4. The cable with the extruded sheath is irradiated through a particle accelerator with an irradiation energy of 1.8 MeV, a running frequency of 40, and an irradiation dose of 15 Mrad. S5. The surface of the cable sheath is laser-etched with patterns such as... Figure 1 The pattern shown has a focal length of 100mm and a scanning speed of 0.6mm / s. The center of the pattern is the non-etched area 1, the pulse energy of the first etched area 2 is 125µJ, and the pulse energy of the second etched area 3 is 165µJ.

[0025] Comparative Example 2 The specific manufacturing process of self-cleaning photovoltaic cables is as follows: S1. Prepare stranded conductors; S2. Use a Φ45+35 single screw extruder to extrude halogen-free cross-linked insulation. Set the screw temperature to 125℃, 130℃, 135℃, 140℃, and 145℃, and ensure that the thinnest point thickness is ≥0.5mm. S3. Use an 80 single-screw extruder to extrude halogen-free crosslinked sheaths, with screw temperatures set to 135℃, 140℃, 140℃, 150℃, 150℃, 150℃, 150℃. S4. The cable with the extruded sheath is irradiated through a particle accelerator with an irradiation energy of 1.8 MeV, a running frequency of 40, and an irradiation dose of 15 Mrad. S5. The self-cleaning coating is prepared from the following raw materials in the indicated mass percentages: 40% waterborne polyurethane dispersion, 11.6% acrylic emulsion, 4.4% composite film-forming agent, 0.4% dispersant, 0.3% defoamer, 0.1% wetting agent, 2% matting agent, 0.2% leveling agent, 0.2% composite thickener, 4% ethanol, 16.8% pure water, and 20% superhydrophobic additive.

[0026] S6. Apply the above self-cleaning coating evenly to the surface of the cable sheath using a spraying method, and then dry it with hot air at 60℃.

[0027] Comparative Example 3 The specific manufacturing process of photovoltaic cables is as follows: S1. Prepare stranded conductors; S2. Use a Φ45+35 single screw extruder to extrude halogen-free cross-linked insulation. Set the screw temperature to 125℃, 130℃, 135℃, 140℃, and 145℃, and ensure that the thinnest point thickness is ≥0.5mm. S3. Use an 80 single-screw extruder to extrude halogen-free crosslinked sheaths, with screw temperatures set to 135℃, 140℃, 140℃, 150℃, 150℃, 150℃, 150℃. S4. The cable with the extruded sheath is irradiated through a particle accelerator with an irradiation energy of 1.8 MeV, a cycle of 40, and an irradiation dose of 15 Mrad.

[0028] Performance testing The cables prepared in the examples and comparative examples were subjected to contact angle tests, and the results are shown in Table 1.

[0029] Table 1 Contact Angle Test Results Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Contact angle (°) 168.7 167.8 163.8 156.3 157.4 97.0 The results above show that the cable prepared in the example has a contact angle of over 163°, exhibits good hydrophobicity, and thus achieves a good self-cleaning effect.

[0030] The cable of Comparative Example 3, which was not laser-etched, had a contact angle of 97.0° and was not hydrophobic.

[0031] The contact angle is 156° when chemical crosslinking and laser etching are combined (Comparative Example 1), and 157.4° when irradiation crosslinking and self-cleaning coating are combined. Both have a certain degree of hydrophobicity, but their effects are worse than those of the present invention.

[0032] The thermal elongation data of the crosslinked sheath before and after laser etching in Example 1 and Comparative Example 1 are shown in Table 2.

[0033] Table 2 Thermal elongation data of the cross-linked sheath before and after laser etching

[0034] Comparing the thermal elongation data of the cross-linked sheath before and after laser etching, it can be seen that the variance and standard deviation of the data under load and permanent deformation in Example 1 did not change significantly, while those in Comparative Example 1 showed significant improvement. This indicates that the data dispersion of Comparative Example 1 increased, suggesting that laser etching caused local over-crosslinking of the chemically cross-linked sheath material, thus affecting the consistency of the crosslinking degree of the sheath.

[0035] The preferred embodiments of the present invention have been described in detail above with reference to the examples. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0036] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable way without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0037] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A method for preparing a self-cleaning photovoltaic cable, characterized in that, The cable comprises a conductor, a halogen-free cross-linked insulation layer, and a halogen-free cross-linked sheath layer, and the preparation method includes the following steps: S1. A halogen-free cross-linked insulation layer and a halogen-free cross-linked sheath layer are sequentially coated on the outside of the cable conductor, and then irradiated. S2. A concentric pattern is laser-etched on the surface of the halogen-free cross-linked sheath layer. The concentric pattern includes a non-etched area and at least two etched areas from the center outwards. The pulse energy of the etched area gradually increases from the center outwards.

2. The preparation method according to claim 1, characterized in that, In step S2, the concentric patterns are concentric circles or concentric regular polygons, and the spacing between each pattern is the same.

3. The preparation method according to claim 2, characterized in that, The concentric pattern is a square.

4. The preparation method according to claim 1, characterized in that, In step S2, the concentric pattern includes a non-etched area, a first etched area, and a second etched area from the center outwards. The focal length of the laser etching is 100~300mm, the scanning speed is 0.6~0.8mm / s, the etching pulse energy of the first etched area is 120~125µJ, and the etching pulse energy of the second etched area is 160~165µJ.

5. The preparation method according to any one of claims 1 to 4, characterized in that, In step S1, the halogen-free cross-linked insulation layer is extruded over the conductor by a single-screw extruder. The screw temperature is set to 125±10℃, 130±10℃, 135±10℃, 140±10℃, and 145±10℃, and its thinnest point thickness is guaranteed to be ≥0.5mm.

6. The preparation method according to any one of claims 1 to 4, characterized in that, In step S1, the halogen-free cross-linked sheath layer is extruded over the halogen-free cross-linked insulation layer by a single screw extruder, and the screw temperature is set to 135±10℃, 140±10℃, 140±10℃, 150±10℃, 150±10℃, 150±10℃, 150±10℃.

7. The preparation method according to any one of claims 1 to 4, characterized in that, In step S1, the irradiation is: irradiation energy of 1.2~2.4MeV, number of operation channels of 24~48, and irradiation dose of 14~15Mrad.

8. A self-cleaning photovoltaic cable prepared by any one of claims 1 to 7.

Citation Information

Patent Citations

  • Mould processing equipment for electrical insulation part production and processing method thereof

    CN122210522A